Identification of emerging harms due to COVID-19 outbreak: a qualitative study in Iran - Sina Ahmadi; Seyed Fahim Irandoost; Neda SoleimanvandiAzar; Marzieh Nojomi; Javad Yoosefi Lebni; Arash Tehrani-Banihashemi (BMC Public Health, 2025)
Abstract Introduction Although COVID-19 has altered various harms and exacerbated the prevalence of some of them, this period has also set the stage for the emergence of new harms. The present study aims to identify the emerging harms resulting from the COVID-19 outbreak in Iran. Methods The study was conducted using a qualitative content analysis approach through semi-structured interviews with 21 experts and professors knowledgeable about social harms and COVID-19 consequences who were selected through purposive and theoretical sampling. Data analysis was carried out using the Graneheim and Lundman’s method in MAXQDA-2018 software. Guba and Lincoln’s criteria were used to trustworthiness of results. Results The results showed that the COVID-19 pandemic led to a range of issues and problems at various levels of society that were not considered social harms before the pandemic, given their prevalence and impact. After analyzing the data, four main categories and fourteen subcategories were identified. The main categories were social fatigue, ineffective education system, formation of a digital lifestyle, and formation of a new understanding and meaning of death and life. Conclusion The COVID-19 crisis has intensified existing social harms and introduced new ones, rendering previous mitigation strategies ineffective. Designing novel policies and guidelines is crucial to address these evolving challenges and reduce the adverse societal impacts of the pandemic.